A case with eosinophilic cholangitis which presented the unique cholangioscopic findings. (27th November 2020) - Hirata, Hajime; Kuwatani, Masaki; Mitsuhashi, Tomoko
Abstract : Highlight Hirata and colleagues report a case of eosinophilic cholangitis with unique cholangioscopic findings including whitish nodules with neither irregular vessels nor atypical mucosa, which differed from those in a previous case. Cholangioscopy enables direct visualization of diverse findings of biliary disease and accurate biopsy for small lesions in the bile duct.